Respostas

  • Usuário do Brainly
2013-01-10T22:07:20-02:00

A regra da divisão é dada por:

 

\text{y}=\dfrac{\text{f}}{g}}

 

\text{y}'=\dfrac{\text{f}'\cdot\text{g}-\text{f}\cdot\text{g}"}{\text{g}^2}

 

Desta maneira, podemos afirmar que:

 

\text{f}=(2+\text{x})~\wedge~\text{g}=(\text{x}-2)

 

Substituindo na regra, tém-se:

 

\text{y}'=\dfrac{[1\cdot(\text{x}-2)-(\text{x}+2)]}{(\text{x}-2)^2}

 

Donde, segue:

 

\text{y}'=\dfrac{\text{x}-2-\text{x}-2}{\text{x}^2-4\text{x}+4}

 

\text{y}'=\dfrac{-4}{(\text{x}-2)^2}